2015
DOI: 10.3906/biy-1403-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide distribution of superoxide dismutase (SOD) gene families inSorghum bicolor

Abstract: Superoxide dismutases (SODs) are critical enzymes protecting cells against toxic superoxide radicals. To date, 3 types of SODs have been identified: Cu-ZnSODs, Fe-MnSODs, and NiSODs. In this study, a genome-wide analysis was performed in Sorghum bicolor to characterize SOD genes and proteins. Using several bioinformatics tools, we characterized a total of 8 SOD genes from the Sorghum genome. Gene structure, chromosomal distribution, tissue specific expression, conserved domain, and phylogenetic analyses of SOD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
59
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 34 publications
16
59
0
Order By: Relevance
“…In a very recent study, six Cu/Zn-SODs and two Fe-SODs were identified in grapevine and the expression analysis established a clear correlation of these genes in light stress resistance as well as in different aspects for abiotic stress management [33]. Other recent studies demonstrated a key role of SODs towards different environmental stresses in plants, such as ethylene, salinity, drought and low temperature [34,35] in various monocots and dicots species including Arabidopsis thaliana [36], Dimocarpus longan [34], Sorghum bicolor [37], Populus trichocarpa [38], Musa acuminate [33], Gossypium raimondii and Gossypium arboreum [39].…”
Section: Figurementioning
confidence: 75%
“…In a very recent study, six Cu/Zn-SODs and two Fe-SODs were identified in grapevine and the expression analysis established a clear correlation of these genes in light stress resistance as well as in different aspects for abiotic stress management [33]. Other recent studies demonstrated a key role of SODs towards different environmental stresses in plants, such as ethylene, salinity, drought and low temperature [34,35] in various monocots and dicots species including Arabidopsis thaliana [36], Dimocarpus longan [34], Sorghum bicolor [37], Populus trichocarpa [38], Musa acuminate [33], Gossypium raimondii and Gossypium arboreum [39].…”
Section: Figurementioning
confidence: 75%
“…SOD plays important roles in multiple processes of plant growth and resistance against environment stresses, and SOD gene family has been reported to be widely distributed in different plant species, such as Arabidopsis [ 40 ], longan [ 41 ], rice [ 34 , 42 ], poplar [ 22 ], banana [ 10 ], sorghum [ 35 ], tomato [ 6 ], and cotton [ 36 , 43 ]. However, no comprehensive analysis of this gene family has been reported in cucumber.…”
Section: Discussionmentioning
confidence: 99%
“…Ferritin is located in plastids and represents important intracellular storage form for Fe [17][18][19]. Mn is essential for the oxygen evolution in photosystem II and for a series of enzymatic reactions (e.g., phosphoenolpyruvate carboxykinase, and superoxide dismutase) [1,2,13,[20][21][22]. Cu is present in the plastidial plastocyanin, in the mitochondrial cytochrome c oxidase, in Cu-Zn superoxide dismutase as well as in a series of other proteins [1,2,13,[23][24][25][26].…”
Section: Heavy Metals: Micronutrients or Pollutants?mentioning
confidence: 99%